Produção de porta-enxertos de mangueira cultivar coquinho - Coutinho, Givago (2014)
CHAPTER I: Aiming to evaluate factors for application in the development of high quality rootstock, two experiments were conducted in protected environment (glasshouse). Factors such as either the presence or absence of the endocarp on the seed, sources of substrate and different concentrations of poultry litter present in the substrate were evaluated as to their influence on the quality and development of the rootstocks. Substrates of common accessible and utilization among the farmers, such as commercial substrate and poultry litter, were used. The works were conducted at the UFU Fruit culture Sector in Uberlândia/MG. In the first experiment, substrates were evaluated (commercial substrate, soil and soil with addition of 25 % of poultry litter vv-1) and their influence on the development of rootstocks with the utilization of seeds either in the presence or absence of the endocarp. Through the results obtained, it was also found that the process of removal of the seed endocarp favored the development of rootstocks, which occurred in a faster way, helping for them to reach the grafting point earlier than the others. However, from among the substrates used, there were no significant differences among them. As to the substrates, there were no significant differences among them, it follows thus, in a general manner, that there was no direct influence of them upon the development of the rootstocks. CHAPTER II: With the objective of evaluating the development as well as the quality of rootstocks of mango tree, cultivar Coquinho, produced on different sources of substrates in the combination with the seed either in the presence or absence of the endocarp, this work was conducted. The experimental design utilized was with randomized blocks in split plots in time with six treatments and six replications each. In each experimental unit were assessed five containers, each containing a rootstock. The treatments were constituted by the factors presence or absence of the endocarp on the seed in combination with the source of substrate used (soil, soil with the addition of poultry litter at 25 % and commercial substrate). The following characteristics were evaluated: height, stem diameter at stem base height and number of leaves. The evaluations were performed at 60, 75, 90, 105 and 120 days after sowing (DAS), afterwards at the completion of the field measurements, the shoots of the rootstocks were collected and the weighing for obtaining the fresh mass (MF) was proceeded and next the drying of the samples in oven at 65 °C for determination of the dry matter (DM). In relation to the results obtained, it was found that there was no significant difference among the substrates used. Regarding the seeds, there was difference in relation to the removal of the endocarp which was significantly superior and contributed by promoting the growth of the rootstocks in a general manner. CHAPTER III: This study aimed to determine the optimal concentration of poultry litter in addition to soil for production of rootstocks mango Coquinho. The experimental design was randomized blocks in split plot design with six treatments and five replications with one plant per container. The treatments consisted of the addition of chicken manure to soil concentrations of addition of poultry litter in a 5:1 ratio , respectively ( 20 % of poultry litter), addition of chicken manure in the ratio of 3:2 (40 % broiler litter) and soil without addition of poultry litter . The soil used was from subsurface horizons. The substrates were combined with Coquinho mango seeds to grow in the presence and absence of the same core material. Height, stem diameter in the lap height and number of leaves expanded to 60, 75, 90, 105 and 120 days after sowing: the characteristics were evaluated. After the last evaluation at 120 DAS proceeded to shoot harvesting of rootstocks for weighing of fresh mass (FM) and subsequently drying the samples in an oven at 65 °C for weighing the dry matter (DM). The originating rootstock seeds in the absence of endocarp showed faster development compared with those that were seeded endocarp. No significant difference between concentrations of poultry litter.